Structural and electrical properties of (Zr,Ti)(0.85)(Ca,Sr)(0.15)O-1.85 thin films grown on Cu/Ti/SiO2/Si substrate using RF magnetron sputtering - Im, Mir; Lee, Tae-Ho; Kweon, Sang-Hyo; Kang, Chong-Yun; Nahm, Sahn (세라믹공정연구센터, 2016)
(Zr,Ti)(0.85)(Ca,Sr)(0.15)O-1.85 (ZTCS) films grown on Cu electrode at room temperature showed a crystalline cubic stabilized ZrO2 structure when large sputtering powers (>= 75 W) were used. The smoothest film, grown at sputtering power of 75W, showed the lowest leakage current (4.0 x 10(-6) A/cm(2) at 0.75 MV/cm) and highest breakdown voltage (2.7 MV/cm) among all the films prepared, indicating that surface roughness considerably influences the electrical properties of the ZTCS film. A dielectric constant (k) of 21.5 and a tan delta of 0.007 were obtained at 100 kHz, and a similar k of 19.4 with a high quality factor of 52 at 2.0 GHz. Moreover, a high capacitance density (78 nF/cm(2)) and a small TCC (256 ppm/degrees C at 100 kHz) were obtained. Such a ZTCS film therefore satisfies the requirements of the International Technology Roadmap for Semiconductors for capacitors grown on organic substrates for 2016.